Peran Guru Pendidikan Agama Islam dalam Membentuk Kepribadian Siswa di MTs Nurul Ikhlas Bekasi - Salsabila Salsabila; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (ISLAMIKA, 2022)
Personality is the overall attitude, expression, feeling, characteristic, and behavior of a person. The attitude, feeling, expression and temperament will manifest in a person's actions when faced with certain situations. Instilling good habits as early as possible is very important for students as well as personality that determines whether students will become good students or vice versa. Teachers are people who have a very important role in schools, especially Islamic Religious Education teachers who are educators who are responsible for shaping students' personalities. This study aims to determine the role of Islamic religious education teachers in shaping the personality of students in MTs. Nurul Ikhlas. The method used is a qualitative research method that has natural characteristics with data sources from observation, documentation and interviews. The results of this study indicate that there are 3 roles of Islamic religious education teachers in shaping the personality of students in MTs. Nurul Ikhlas, namely the teacher as a guide, the teacher as a role model and the teacher as the giver of punishment and rewards, these three roles are quite influential in shaping the personality of students in MTs. Nurul Ikhlas. The supporting and inhibiting factors in shaping the personality of students in MTs. Nurul Ikhlas is one of them getting support from school principals and foundations. While the inhibiting factors are the lack of concentration of students while studying so that students do not understand what material is conveyed by the teacher and the lack of support from students' parents because students are not allowed to bring cellphones or other communication tools to school.